2020
DOI: 10.2340/1650197795278998
|View full text |Cite
|
Sign up to set email alerts
|

A clinical method for measuring segmental flexion mobility in the cervico-thoracic spine and a model for classification

Abstract: Pain and limitation of spinal mobility are symptoms frequently reported by patients. Many methods have been used to assess the total range of mobility in the different parts of the spine, but there is no method for clinical examination of segmental mobility. The aim of this study was to describe such a technique concerning of segmental flexion mobility in the cervico-thoracic spine, C7-T5, and to present a model for classification of mobility. The results of this study show that the relative flexion mobility e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…We found a linear regression similar to ours in the study by Norlander et al (1995). They validated the use of a tape measure for skin distraction (Schober's test) in assessing segmental mobility of the thoracic spine using the inclinometer (n = 42) and found a positive linear relationship between spine flexion mobility at the T1 and T8 level (in degrees) and Schober's test (in centimeters) (R 2 = .48; p < .001; R 2 = .44; p < .001), data similar to the results found in our study.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We found a linear regression similar to ours in the study by Norlander et al (1995). They validated the use of a tape measure for skin distraction (Schober's test) in assessing segmental mobility of the thoracic spine using the inclinometer (n = 42) and found a positive linear relationship between spine flexion mobility at the T1 and T8 level (in degrees) and Schober's test (in centimeters) (R 2 = .48; p < .001; R 2 = .44; p < .001), data similar to the results found in our study.…”
Section: Discussionsupporting
confidence: 90%
“…However, the method is commonly applied in the lumbar region, but the thoracic Schober test is less studied, and despite being a validated and low-cost clinical tool, few studies correlate the Schober test with other chest spine evaluation instruments, such as the inclinometer. Despite the scarcity of studies that have evaluated thoracic spine mobility, we found a similar correlation and simple linear regression results between the Schober test and the inclinometer for thoracic spine mobility in the study by Norlander et al (1995). Despite being older, this study provides a relevant clinical method to measure the distribution of segmental flexion of mobility in the thoracic spine.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…When the thoracic spine has limited rotational ROM, substantial movement from the scapulothoracic and glenohumeral joints is required, causing muscle and strength imbalances and an elevated risk of injury 7 ) . Furthermore, there are documented cases of thoracic spine hypomobility contributing to neck symptoms 8 , 9 ) and low back pain 10 ) . These findings emphasise the interconnectedness of spinal health and potential ripple effects throughout the musculoskeletal system.…”
Section: Introductionmentioning
confidence: 99%